A survey of insect pest and beneficial arthropod species in organic and inorganically grown paddy in West Johor / Harushani Parzi - Parzi, Harushani (Faculty of Plantation and Agrotechnology, 2015)
The study was conducted at non-granary growing paddy area in Johor and Malacca for a season May to August 2014. Insect sampling was done by using sweep net, yellow sticky trap and water pan trap for two plot of fragrant variety planted by semi –organic and inorganic practices. From the study, 31 arthropod species was identified. From that 16 species is categorized as insect pests while 9 species is the beneficial insects that act as natural enemies toward pest species. Another 6 species is categorized as others since they are not pest and not cause any harmful to paddy. Nephotettix virescens, Nilaparvata lugens, Hydrellia philippina, and Recilia dorsalis, in that order of abundance, are considered as the major pests of paddy in the studied locations. Species from order Odonata (damselflies) and Araneae (spiders) are the two most important predatory group (natural enemies) possibly controlling the insect pest population. Analysis of variance at for mean different shows that there is no significant of arthropod abundance between semi-organic and inorganic planting practice, and for each of the 2 major groupings- pests, and natural enemies. Pests that identified have significant different among three growth stages are Green leafhopper-Nephotettix virescens, Brown planthopper- Nilaparvata lugens, Rice leafhopper-Cnaphalocroeis medinalis, Herpetogramma aeglealis, Spodoptera exigua (larvae), Xanthopimpla flavolineata-Cameron, and Reeilia dorsalis. Demsflies- Aciagrion borneense, Long-jaw spider- Tetragnatha maxillosa thorell, and Paederus fuscipes Curtis are the natural enemies species that have significant different among three growth stage. Findings indicate that pesticides application in inorganic cultivation have adverse effect toward beneficial species population. Semi-organic inputs should be encouraged if it does not drastically affect yield. Thus it will enhance the reducing of chemical usage that contributes to sustainability of agriculture.